INTEGRATED BORDER MANAGEMENT TO ACHIEVE COMMUNITY WELFARE OF KEPULAUAN RIAU PROVINCE - Rusmiyati Rusmiyati; Mesy Faridah Hendiyani; Afni Nooraini; Alma'arif Alma'arif (Universitas Padjadjaran, 2022)
ABSTRACT. Border area as a front line of a country needs special attention from the government of that country. Most of the domestic problems experienced by a country come from the border. Human and drugs trafficking, also illegal timber transactions are examples of problems that still occur in Indonesia nowadays especially located in Kepulauan Riau Province. This study aims to describe the Integrated Border Management based on European Commission carried out in Indonesia, especially at the country border in Kepulauan Riau Province, Indonesia. By using the post-positivistic paradigm, this study uses interviews and documentation as data collection techniques. Interviews were conducted to actors, both central and regional, such as the Deputy for Border Management (BNPP-RI), the Head of the BNPP Planning and Cooperation Bureau, the Head of the Riau Islands Province Government Bureau and his staff, the Head of Local Development Planning Agency of Batam City, Natuna Regency. The results showed that the state border managers at the central, provincial, and regency/city governments have different institutions which result in differences in personnel procedures, finances, and resource allocation. The concept of Integrated border management needs to be adjusted to the concept considering the geographical characteristics of Indonesia, which has sea and land borders.